The haloes and environments of nearby galaxies (HERON): III. A 45-kpc spiral structure in the GLSB galaxy UGC 4599 - Mosenkov, Aleksandr; Rich, R Michael; Fusco, Michael; Kennefick, Julia; Thilker, David; Marchuk, Alexander; Brosch, Noah; West, Michael; Gregg, Michael; Longstaff, Francis; Koch-Hansen, Andreas; Abdeen, Shameer; et al. (Monthly notices of the Royal Astronomical Society, 2023)
We use a 0.7-m telescope in the framework of the Halos and Environments of Nearby Galaxies (HERON) survey to probe low surface brightness (LSB) structures in nearby galaxies. One of our targets, UGC 4599, is usually classified as an early-type galaxy surrounded by a blue ring making it a potential Hoag’s Object analogue. Prior photometric studies of UGC 4599 were focused on its bright core and the blue ring. However, the HERON survey allows us to study its faint extended regions. With an 8-h integration, we detect an extremely faint outer disc with an extrapolated central surface brightness of μ0, d(r) = 25.5 mag arcsec−2 down to 31 mag arcsec−2 and a scale length of 15 kpc. We identify two distinct spiral arms of pitch angle ∼6○ surrounding the ring. The spiral arms are detected out to ∼45 kpc in radius and the faint disc continues to ∼70 kpc. These features are also seen in the GALEX far- and near-ultraviolet bands, in a deep u-band image from the 4.3-m Lowell Discovery Telescope (which reveals inner spiral structure emerging from the core), and in H i. We compare this galaxy to ordinary spiral and elliptical galaxies, giant low surface brightness (GLSB) galaxies, and Hoag’s Object itself using several standard galaxy scaling relations. We conclude that the pseudo-bulge and disc properties of UGC 4599 significantly differ from those of Hoag’s Object and of normal galaxies, pointing toward a GLSB galaxy nature and filamentary accretion of gas to generate its outer disc.
Veröffentlicht: 21. August 2023
Gesehen am 14.11.2023